Quantitative Fragrance Durability Evaluation Depending on Keeping Condition of Knitted Fabric Treated by Microcapsule Containing Star Anise Essential Oil - Chu, Dieu Huong; Nguyen, Thi Tu Trinh (JST: Engineering And Technology For Sustainable Development, 2022)
Fabric treated by fragrance was one of textile applications. The evaluation of fragrance durability of fabric treated by the fragrance was always the subject of many researches, though quantitatively determining fragrance intensity was difficult and there will not always be agreement on odor characteristics by difference testers. In this paper we build a simple and quantitative method to evaluate the fragrance intensity, which could consider as the remained oil quantity on fabric treated by microcapsule loaded by Star Anise essential oil. The evaluation was based on the combination of the expert method and diluted solution method. This method was used to evaluate an influence of the knitted fabric’s keeping conditions on fragrance duration of fabric. Two groups of single jersey fabric have been prepared: ones were knitted from the Ne 40/1 CVC yarn (60% cotton and 40% polyester). The second group was also single jersey fabrics knitted from the Ne 46/1 100% cotton. The knitted fabrics treated by microcapsule containing star anise essential oil and then have been kept in ambient condition (temperature was about 25°C ±2, relative humidity was 75% ±2) and in the cold dried condition (temperature was about 2°C, relative humidity was 20%). The results showed that the developing method in the research can use to effectively quantitatively evaluate the fragrance intensity of fabric treated by fragrance. The fabrics treated by microcapsule containing Star Anise oil essential remain their fragrance longer than 7 days in the cool dried condition while which ones in the ambient condition finished their fragrance on 5 days.